Baumgarten’s Shift in Rationality. An Analysis through the Notion of “Extensive Clarity” - Hereza-Modrego, David (Con-Textos Kantianos. International Journal of Philosophy, 2025)
The birth of aesthetics in Baumgarten is usually understood either as a continuation of Leibnizian-Wolffian rationalism or as a rupture towards a proto-irrationalism. Neither of these interpretations proves adequate, for what is decisive in his work consists in a shift with respect to tradition that redefines the very idea of rationality. For this, it is hermeneutically necessary to distinguish two senses of confusion in Baumgarten’s work. The rereading of the rational that this distinction enables is what grants its full meaning to the notion of “extensive clarity.